Ginsenoside Rk1 induces apoptosis and downregulates the expression of PD-L1 by targeting the NF-κB pathway in lung adenocarcinoma. Issue 1 (12th December 2019) - Hu, Manling; Yang, Jing; Qu, Linlin; Deng, Xuqian; Duan, Zhiguang; Fu, Rongzhan; Liang, Lihua; Fan, Daidi
Abstract : Ginsenoside Rk1 can function as an antitumor modulator that induces apoptosis in lung adenocarcinoma cells by inhibiting NF-κB transcription and triggering cell cycle arrest. Abstract : Ginsenoside Rk1 is a substance derived from ginseng and exhibits various activities such as anti-diabetic, anti-inflammatory and anti-cancer effects; however, its anti-tumor effect and target signaling mechanism in lung adenocarcinoma are not well understood. Here, we show that Rk1, a natural drug product, can function as an antitumor modulator that induces apoptosis in lung adenocarcinoma cells by inhibiting NF-κB transcription and triggering cell cycle arrest. Mechanistically, Rk1 suppressed the proliferation and clonal formation of two lung adenocarcinoma cell lines (A549 and PC9) in vitro and caused G1 phase cell arrest. In the A549 xenograft model, Rk1 significantly inhibited tumor growth and had few toxic side effects on normal organs. Western blotting results showed that Rk1 increased the protein expression of Bax, cleaved caspase-3, -8, and -9, and PARP, decreased the expression of Bcl-2 and blocked the NF-κB signaling pathway. Furthermore, ginsenoside Rk1 also reduced the high expression of PD-L1 in lung adenocarcinoma cells by inhibiting NF-κB signaling. These data revealed a previously unreported antitumor mechanism of Rk1, providing new ideas and an experimental basis for further study of the mechanism of action of Rk1 in lung adenocarcinoma.